Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1983
DOI: 10.1007/bf00429076
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle tension, flow, pressure, and EMG during sustained isometric contractions in humans

Abstract: In five healthy males sustained isometric torques during elbow flexion, knee extension, and plantar flexion correlated positively with intramuscular tissue pressure (MTP) in the range 0-80% of the maximal voluntary contraction (MVC). During passive compression of the muscle at rest 133-Xenon muscle clearance stopped when MTP reached diastolic arterial pressure (DAP) indicating that the muscle vascular bed was occluded. However, during sustained contraction this relation between DAP, flow and MTP was not seen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
254
5
15

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(287 citation statements)
references
References 14 publications
13
254
5
15
Order By: Relevance
“…In a variety of muscle groups (e.g., elbow flexors, knee extensors, plantar flexors, and dorsiflexors), data collected indirectly using isotope clearance (22), VOP (25), or fMRI (31) suggest that the IMP generated during isometric exercise will occlude MBF at a relative contraction strength of 50 -65% MVC (60% MVC in the dorsiflexors of young males; Ref. 31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a variety of muscle groups (e.g., elbow flexors, knee extensors, plantar flexors, and dorsiflexors), data collected indirectly using isotope clearance (22), VOP (25), or fMRI (31) suggest that the IMP generated during isometric exercise will occlude MBF at a relative contraction strength of 50 -65% MVC (60% MVC in the dorsiflexors of young males; Ref. 31).…”
Section: Discussionmentioning
confidence: 99%
“…IMP is positively related to contraction intensity (22,24); thus, it is held that there is a critical force threshold beyond which mechanical pressure will occlude MBF (24,25,29,30) and below which flow will be affected to varying degrees depending on the contraction intensity and anatomical location (compartmental pressure). Results obtained using a variety of techniques suggest that complete occlusion of MBF and perfusion occur at 50 -60% of maximal voluntary contraction (MVC) force (13,22,25,31). However, relatively few studies have recorded MBF directly during a sustained isometric effort, and the degree to which perfusion is compromised by high-intensity contraction remains uncertain.…”
mentioning
confidence: 99%
“…It was reported that the mean % MVC that would stop muscle blood flow is 50% MVC in the musculus rectus femoris and 64% MVC in the musuclus vastus lateralis (Sadamoto, 1983). Shepard (1983) suggested that isometric contractions that develop less than 15% to 30% MVC, depending on the muscle groups, produce moderate increase in blood flow during contractions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the blood flow in the muscles decreased towards or below the resting level at higher intensities, since intramuscular pressure is positively related to contraction intensity 14,15) . We recently reported that blood volume and oxygen saturation in human tendons could be determined using a laser oxygenation monitor 16) .…”
Section: Introductionmentioning
confidence: 93%